A post-ophiolitic plutonism record in the Central-East Iranian Microcontinent: Evidence for Pre-Eocene age of Neo-Tethys subduction - Marzieh Ghadirpour; Ghodrat Torabi; Nargess Shirdashtzadeh; Thomas C. Meisel; Tomoaki Morishita (Journal of African Earth Sciences, 2025)

Forearc magmatism in the Pannonian basin recorded by metasomatised skarnoid xenoliths in Pliocene basalt (Novohrad-Gemer Volcanic Field, Slovakia) - Luca Reato; Monika Huraiová; Lukáš Ackerman; Jana Ďurišová; Monika Horschinegg; Patrik Konečný; Thomas C. Meisel; Vratislav Hurai (Lithos, 2024)

Green and blue infrastructure as model system for emissions of technology-critical elements - Simone Trimmel; Philipp Spörl; Daniela Haluza; Nagi Lashin; Thomas C. Meisel; Ulrike Pitha; Thomas Prohaska; Markus Puschenreiter; Elmar Rückert; Bernhard Spangl; Dominik Wiedenhofer; Johanna Irrgeher (Science of The Total Environment, 2024)

Subduction zone-related metasomatism of Devonian oceanic lithosphere: Evidence from mineralogical, geochemical, and O-H-Sr isotope characteristics of amphibole-bearing peridotites of the Sowie Mountain Block (SW Poland) - Ahmed H. Ahmed; Mohamed M. Hamdy; Thomas C. Meisel (Lithos, 2024)

To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Elisabeth S. Gruber; Vanessa Stadlbauer; Verena Pichler; Katharina Resch-Fauster; Andrea Todorovic; Thomas C. Meisel; Sibylle Trawoeger; Oldamur Hollóczki; Suzanne D. Turner; Wolfgang Wadsak; A. Dick Vethaak; Lukas Kenner (Exposure and Health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters (“vectors”) of contaminants and as chemosensitizers for toxic substances (“Trojan Horse effect”). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the “culture of consumerism.” Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.

Origin of primary PGM assemblage in сhromitite from a mantle tectonite at Harold’s Grave (Shetland Ophiolite Complex, Scotland) - Inna Yu. Badanina; Kreshimir N. Malitch; Richard A. Lord; Thomas C. Meisel (Mineralogy and Petrology, 2013)

Synthesis of PGE sulfide standards for laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) - Cora C. Wohlgemuth-Ueberwasser; Chris Ballhaus; Jasper Berndt; Vaida Stotter née Paliulionyte; Thomas Meisel (Contributions to Mineralogy and Petrology, 2007)